WSPÓŁCZESNE TENDENCJE W ZAKRESIE METOD WYZNACZANIA PRAWA WŁAŚCIWEGO DLA MAŁŻEŃSKICH STOSUNKÓW MAJĄTKOWYCH - Żarnowiec, Łukasz (Zeszyty Prawnicze, 2016)
Current Trends in the Conflict of Legal Methods in Matrimonial Property Regimes Summary The difficulties relating to the determination of the law applicable to personal and property relations between spouses are one of the most significant barriers to the free movement of individuals between different countries. Due to the importance of matrimonial property regimes for the situation of third parties entering into legal relations with married persons, matrimonial property regimes also have a seminal impact on the security of free movement and exchange. This article presents an analysis of conflict-of-law methods used to determine the law applicable to matrimonial property relations under selected conflict-of-law regulations adopted in different countries, the proposed uniform European regulation, and the former Polish International Private Law Act (Ustawa o prawie prywatnym międzynarodowym) of 1965. It also contains an assessment of the relevance of new conflict-of-law rules that have been introduced at the national level. The article may be regarded as a background for the analysis of the arrangements presented in the new Polish International Private Law Act of 2011, which will be presented in a separate issue of this journal.